Creativity-oriented Approach of Higher Education in Russian Federation - Gladilina, I.P.; Razumovskiy, S.L.; Rumyantseva, E.A.; Sergeeva, S.A.; Vetrova, E.A.; Shadskaja, I.G. (International Review of Management and Marketing, 2016)
The contemporary higher professional education strictly formulates one of the most important goals of science – development of creativity in students. In the creative process only, new ideas are brought, stereotypes holding back the civilizational progress are broken, new approaches are established for social life organization, contributing to the perception of not just simple need for creative work. The formation of the need for creativity in students is a comprehensive process based on conceptualization and perception of Russia's and global cultural and historical experience. Keywords: Creative work, foreign and national concepts of creative work, programs, technologies, higher professional education. JEL Classifications: I21; I23; I25